2006
DOI: 10.2106/jbjs.f.00203
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Autologous Bone-Marrow Grafting for Nonunions

Abstract: Percutaneous autologous bone-marrow grafting is an effective and safe method for the treatment of an atrophic tibial diaphyseal nonunion. However, its efficacy appears to be related to the number of progenitors in the graft, and the number of progenitors available in bone marrow aspirated from the iliac crest appears to be less than optimal in the absence of concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
122
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(134 citation statements)
references
References 4 publications
2
122
0
3
Order By: Relevance
“…After an injection of 2.000 IE heparine, an aspiration and concentration system (Marrowstim Ò , Biomed, Warsaw, IN) was used according to the guidelines of the manufacturer. 19,20 Briefly, 20 mL of bone marrow aspirate were used to create 3 mL of concentrate. The concentrate was transferred in a custom-made cell-seeding device (manufactured by the Institutional Central Research Laboratories of Hannover Medical School (MHH); Fig.…”
Section: Experimental Designmentioning
confidence: 99%
“…After an injection of 2.000 IE heparine, an aspiration and concentration system (Marrowstim Ò , Biomed, Warsaw, IN) was used according to the guidelines of the manufacturer. 19,20 Briefly, 20 mL of bone marrow aspirate were used to create 3 mL of concentrate. The concentrate was transferred in a custom-made cell-seeding device (manufactured by the Institutional Central Research Laboratories of Hannover Medical School (MHH); Fig.…”
Section: Experimental Designmentioning
confidence: 99%
“…The harvest of autologous bone marrow has been developed in previous studies (Bielecki, 2006). Since bone marrow contains osteogenic progenitors, the injection of bone marrow is considered to have the potential for effective bone regeneration (Hernigou, 2006;Undale, 2009). The implantation of bone marrow can increase the local biology and optimize the potential of osteoprogenitors (Ohgushi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs reimplantation was performed using a technique described by Hernigou et al (Hernigou, 2006). Under general anaesthesia, the patient was placed on the operating table in a supine position.…”
Section: Mscs Reimplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for choosing ADSCs was that a high number of stem cells were needed. In human clinical case reports, the injection of bone marrow derived stem cells (BDSCs) in atrophic tibia nonunion fractures have elicited successful bone healing, and it has been suggested that the efficacy of bone healing appears to be related to the number of osteoprogenitor cells injected (Hernigou et al, 2006). Adipose tissue was chosen as the stem cell source because it has a large number of stem cells compared with bone marrow.…”
Section: Discussionmentioning
confidence: 99%